FAKTOR RISIKO KEJAIDAN INFEKSI CACINGAN - Muhammad Heickal Ikhlasul Amal Arrizky (Yayasan Pendidikan Medika Indonesia, 2021)
Infection of worms are one of the intestinal parasitic infections. This infection causes the greatest morbidity worldwide, especially in developing countries. The most common cause is soil-transmitted helminths (STH). STH infection causes 9000 to 135000 deaths per year in the world. Chronic and asymptomatic morbidity in children is associated with STH infection. The purpose of this paper is to determine the risk factors for the incidence of intestinal worm infection in children. The method used is a literature review by searching for the keywords intestinal worms, STH infections, and children on Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion and comparison of the results presented in the article. From several studies conducted, the risk factors for the incidence of worm infection in children include the habit of washing hands, the habit of activities on the ground without using footwear, nail hygiene, SPAL (Wastewater Disposal Facility), water cleanliness, use of latrines, waste processing, floor conditions , level of knowledge, parental occupation, and use of deworming medication.